sosialisasi prosedur dan manfaat pembiayaan emas bagi Nasabah di Bank Syariah Indonesia KCP Pandaan Pasuruan - Hirda Prastira; Wirda Isti'anatuz Zulfa; Lailatul Maslakhah; Afidatu Aininnisa; Sukamto (LPPM ITB AAS Indonesia Surakarta, 2026)
Public literacy regarding Sharia-compliant gold financing products is stillrelatively low, leading to misperceptions regarding the application procedures andbenefits of halal investments at Bank Syariah Indonesia (BSI) Pandaan Branch Office,Pasuruan. This community service activity aims to improve customer and prospectivecustomer understanding of the procedures, contracts, and economic and shariacompliant benefits of gold financing through a participatory and educational approach.The outreach program was conducted in November 2025 in the Pandaan area with thecoordination center at BSI Pandaan Branch Office, involving four implementers: Hirda,Wirda, Fida, and Lail. The implementation method included identifying needs throughinitial interviews, developing simple materials, educational presentations, two-waydiscussions, simulating the application process, distributing brochures, and evaluatingthrough a quick survey. The results of the activity showed a significant increase inparticipant understanding, including an increase in understanding of financingprocedures from 45% to 85%, understanding of benefits from 50% to 88%, and anincrease in interest in applying in the next three months from 35% to 72%. Thesefindings indicate that interactive educational methods based on simulations anddiscussions are effective in increasing literacy, reducing perceived process complexity,and increasing trust in financing products. However, this activity has severallimitations: participants can only be present in the bank area and the evaluation canonly be conducted within a short time. Overall, this program is a strategic effort toincrease knowledge about Islamic finance and halal investment culture in the Pandaancommunity.Keywords: Gold financing, Islamic financial literacy, educational socialization,Bank Syariah Indonesia, halal investment, Pandaan